From grape to wine: Changes in phenolic composition and its influence on antioxidant activity - Lingua, Mariana Soledad (2016)
The evolution of phenolic compounds and their relationship with the antioxidant capacity (AC) of samples taken along the winemaking process of three Vitis vinifera L. cv., Syrah, Merlot and Cabernet Sauvignon grown in Argentina were studied. Forty five compounds were identified by HPLC-PDA-MS/MS, while the AC was determined by FRAP, ABTS and DPPH assays. Results show that phenolic composition and AC vary along the winemaking process and between varieties. Multiple regression analysis showed a high correlation between phenolic composition and AC of samples, being anthocyanins the main family with significant contribution to AC. In addition, quantitative differences in specific phenolic compounds help to explain differences in AC observed between varieties. A high phenolic content and bioactivity still remain in pomaces which support its use as an inexpensive source of antioxidants.